A Study of Youth Volleyball Players Participation Motivation and Relate Elements - Zeng, Howard Z.; Meng, Wen-Yan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
The present study examined the essential factors that truly motivated youth athletes participated in Volleyball practices and competitions using the Adapted Questionnaire of Volleyball Athletes Motivation-Chinese Version. Participants were 92 youth volleyball athletes (age 14-17) from 15 schools of Nanjing City, China. Data analysis was done by a 2 Gender (boy or girl) x 2 Education-levels (high-school or middle-school) x 2 School-types (sport-school or regular-school) multivariate analysis of variance (MANOVA). Findings included: the top five higher scores from the 19 RFs were: RF1 Technical-content and unique-value M ± SD = 4.30 ± .83; RF17 For extraordinary-skills M ± SD = 4.24 ± 1.04; R3 For health M ± SD = 4.11 ± 1.02; RF12 Improve own-literacy M Â± SD = 4.00 ±1.26; RF9 become healthier M± SD = 3.58 ±1.13. These RFs possess significant higher impact on the participantsmotivations. The results of the MANOVA revealed that: two out of three independent variables reached meaningful significantly difference level (p < .00), wherein in Genderaspect, Î› = .37, F = 5.92 with boys athletes motivation score significantly higher (p < .00) than the girls athletes; (2) in School-types aspect, Î› = .24, F =11.17 with sport-school players motivation score significantly higher (p < .00) than the regular-school players.